ANALYSIS OF FACTORS AFFECTING PRODUCTION EFFICIENCY IN THE MANUFACTURING INDUSTRY - Tandiawan, Vira; Seran, Serlin; Masud, Masdar (International Journal of Economics, Business and Accounting Research (IJEBAR), 2024)
The analysis of production factors in PT X's industrial processing is crucial for increasing inter-sector value addition and making a substantial contribution to the regional GDP in economic development. Collaborations between regions can lead to the concentration of processing industries or industrial agglomerations in Central Java. Regions with potential access to natural resources as raw materials and skilled human resources can benefit from economies of scale, economic location, and nearby labor to boost regional economic growth. Optimizing the substitution of production factors is considered in input usage, with a substitution elasticity of 1. Production efficiency is measured through technical, price, and economic efficiency, along with returns to scale. This research aims to analyze input usage and include exogenous factors like industrial agglomeration. The analysis method uses Stochastic Frontier Analysis (SFA) with Frontier 4.1 software estimation. The study's findings reveal significant positive influences of capital (X1), raw materials (X3), labor (X3), wages per labor (X4), and agglomeration (AG). The conclusion underscores the proportional addition of production factors to achieve optimal production scale results. Updating production machinery faces challenges from modern technological developments that enhance production outcomes. Improving human resource quality through training and formal education, making it labor-intensive, helps absorb a substantial workforce.